Coverage of the elections of April, 1975 in the Diário de Notícias and the Jornal Novo: a case study - Lima, Helena; Luis, Rita (RIHC. Revista Internacional de Historia de la Comunicación, 2018)
The Portuguese Revolution of April 1974 ended 48 years of dictatorship. The political evolution that followed the coup gave rise to a revolutionary process, the On-Going Revolutionary Period, which gained momentum, after March 11, 1975, opening "the path to socialism". As a side effect, the state became the owner of almost all the press. The first democratic elections took place on April 25, 1975. For the first time in almost 50 years, the press had the opportunity to do the cover in an environment of freedom of expression. However, the media were not immune to the revolutionary process and the newspapers were affected by the struggle for control of the information. The purpose of this study is a first approach in order to understand the news process and strategies to cover the electoral campaign in the press. The methodology will rely on a comparative analysis of the journalist formats in Diário de Notícas and Jornal Novo, chosen for de difference of each journalistic format and almost opposite editorial status